Faktor Determinasi Kualitas Audit: Studi Empiris pada Entitas yang Listing di Bursa Efek Indonesia Priode 2015 - 2019 - Rahmat Fauzi; Charoline Cheisviyanny; Dovi Septiari (Jurnal Eksplorasi Akuntansi, 2022)
This study aims to determine and find out about the audit quality of companies listed on Bursa Efek Indonesia from 2015 to 2019. in taking samples in this study using purposive sampling method. The data used in this study is the annual report of companies listed on the Bursa Efek Indonesia obtained from the Bursa Efek Indonesia website and the website of each sample company, testing is done by using regression. The results showed that Auditor Industry Specialization had a positive effect on audit quality, Audit Fees had no significant effect on audit quality, Audit Delay had a positive effect on audit quality, New Clients had no significant effect on audit quality, and KAP Size (Big 4 or Non Big 4) does not have a significant effect on audit quality and the number of clients has a negative effect on audit quality in companies listed on the Bursa Efek Indonesia in 2015-2019.